2021
DOI: 10.1080/14756366.2021.1924165
|View full text |Cite
|
Sign up to set email alerts
|

Is carbonic anhydrase inhibition useful as a complementary therapy of Covid-19 infection?

Abstract: The ongoing Covid-19 is a contagious disease, and it is characterised by different symptoms such as fever, cough, and shortness of breath. Rising concerns about Covid-19 have severely affected the healthcare system in all countries as the Covid-19 outbreak has developed at a rapid rate all around the globe. Intriguing, a clinically used drug, acetazolamide (a specific inhibitor of carbonic anhydrase, CA, EC 4.2.1.1), is used to treat high-altitude pulmonary oedema (HAPE), showing a high degree of clinical simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…Patients affected by COVID-19 could show a dysregulated acid–base status probably influenced by the CA activity, which is highly increased in patients affected by COVID-19 infection. Thus, these compounds could be useful as an adjunctive pharmacological treatment for COVID-19 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients affected by COVID-19 could show a dysregulated acid–base status probably influenced by the CA activity, which is highly increased in patients affected by COVID-19 infection. Thus, these compounds could be useful as an adjunctive pharmacological treatment for COVID-19 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 patients demonstrate a dysregulated acid-base status affected by increased CA activity. It has been demonstrated that dexamethasone decreases CA9 expression via the HIF-1α-dependent mechanism; thus, classical CA inhibitors (e.g., acetazolamide and methazolamide) could be used as an adjunctive treatment for COVID-19 patients; for example, acetazolamide treatment improved respiratory conditions in COVID-19 patients in a clinical study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Mumoli et al [24] at hospital admission of 88 COVID-19 patients, as well as by Doaei et al [25], who measured similar values of the blood gas parameters in critically ill patients with COVID-19 to those reported in our study. On the other hand, Deniz et al [26] detected a mild increase of pH and bicarbonate and relatively low pCO 2 in COVID-19 patients compared with non-COVID-19 individuals.…”
Section: Clinical Laboratory Parameters Abnormalities In Moderate And...mentioning
confidence: 93%